2021
DOI: 10.1051/0004-6361/202039898
|View full text |Cite
|
Sign up to set email alerts
|

A MeerKAT view of pre-processing in the Fornax A group

Abstract: We present MeerKAT neutral hydrogen (H I) observations of the Fornax A group, which is likely falling into the Fornax cluster for the first time. Our H I image is sensitive to 1.4 × 1019 atoms cm−2 over 44.1 km s−1, where we detect H I in 10 galaxies and a total of (1.12 ± 0.02) × 109 M⊙ of H I in the intra-group medium (IGM). We search for signs of pre-processing in the 12 group galaxies with confirmed optical redshifts that reside within the sensitivity limit of our H I image. There are 9 galaxies that show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 112 publications
9
82
1
Order By: Relevance
“…If RPS stripping is contributing to pre-processing in groups, this implies that galaxies infalling onto clusters as part of a group should already be Hi deficient, to some extent, relative to field galaxies. This is consistent with Hi observations from the BUD-HIES survey which find Hi deficient galaxies in group-mass substructures surrounding the Abell 963 cluster (Jaffé et al 2016), as well as MeerKAT observations finding Hi deficient galaxies in the Fornax A group (Kleiner et al 2021). Other works have also reported evidence for Hi deficient galaxies in groups (e.g.…”
Section: Implications For Pre-processingsupporting
confidence: 91%
See 2 more Smart Citations
“…If RPS stripping is contributing to pre-processing in groups, this implies that galaxies infalling onto clusters as part of a group should already be Hi deficient, to some extent, relative to field galaxies. This is consistent with Hi observations from the BUD-HIES survey which find Hi deficient galaxies in group-mass substructures surrounding the Abell 963 cluster (Jaffé et al 2016), as well as MeerKAT observations finding Hi deficient galaxies in the Fornax A group (Kleiner et al 2021). Other works have also reported evidence for Hi deficient galaxies in groups (e.g.…”
Section: Implications For Pre-processingsupporting
confidence: 91%
“…A few more studies have found 'cometlike' Hi morphologies for galaxies in groups (Bureau & Carignan 2002;McConnachie et al 2007), which are likely being driven by RPS. In particular, a recent MeerKAT study of the Fornax A group (Kleiner et al 2021) present evidence for 9 galaxies in the midst of being pre-processed prior to accretion onto the Fornax cluster. Some of these galaxies display Hi deficiencies as well as Hi morphologies consistent with RPS (Kleiner et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many authors, e.g., Dressler (2004), argue that in these environments prolonged exposure to intra-group tidal interactions and "preprocessing" more generally, is more efficient in affecting the cold gas reservoirs of galaxies. Evidence of the impact of preprocessing on the H i in LTGs in a rich infalling group was recently presented in Kleiner et al (2021), see also Cortese et al (2021).…”
Section: Introductionmentioning
confidence: 88%
“…The data analyzed in this work consists of the H i image obtained with MeerKAT and already published by Kleiner et al (2021), together with the polarized image and RM image obtained with ASKAP during commissioning tests of the telescope in view of the Early Science program which covered the Fornax cluster (Anderson et al 2021). The commissioning observations presented here correspond to a different scheduling block with respect to the Fornax cluster observations by Anderson et al (2021).…”
Section: Datamentioning
confidence: 99%